Improved granular materials with cationic asphalt emulsion for pavement sub-bases - Zambrano Mesa, M. Isabel (2025)
The use of bases treated with hydraulic binders or asphalt binders has become a common solution in the construction of pavement bases or sub-bases due to the need to achieve high performance, and also because of the increment of the repetitions and magnitudes of loads in transportation. The treatment with additives provides greater resistance and behavior to the pavement layers over time. A granular material was selected with the purpose of evaluating the effectiveness of one of these treatments. This material did not meet the requirements of a road subbase because of its high plasticity. A cationic asphalt emulsion was incorporated to this granular material in order to check the variations that this treatment could experience regarding its resistance in the laboratory. Finally, good results were obtained with this treatment. An increase in resistance to CBR after immersion and conserved resistance were observed. The modifications produced after the treatments, are also shown by comparing a conventional flexible structure and a structure with a stabilized sub-base layer with an emulsion instead of a non-agglomerate traditional subbase, using an empirical-mechanistic procedure of AASTHO Design Guide.